Early liver retransplantation in adults. (18th October 2013) - Rana, Abbas; Petrowsky, Henrik; Kaplan, Bruce; Jie, Tun; Porubsky, Marian; Habib, Shahid; Rilo, Horacio; Gruessner, Angelika C.; Gruessner, Rainer W. G.
Summary Up to 23% of liver allografts fail post‐transplant. Retransplantation is only the recourse but remains controversial due to inferior outcomes. The objective of our study was to identify high‐risk periods for retransplantation and then compare survival outcomes and risk factors. We performed an analysis of United Network for Organ Sharing (UNOS) data for all adult liver recipients from 2002 through 2011. We analyzed the records of 49 288 recipients; of those, 2714 (5.5%) recipients were retransplanted. Our analysis included multivariate regression with the outcome of retransplantation. The highest retransplantation rates were within the first week (19% of all retransplantation, day 0–7), month (20%, day 8–30), and year (33%, day 31–365). Only retransplantation within the first year (day 0–365) had below standard outcomes. The most significant risk factors were as follows: within the first week, cold ischemia time >16 h [odds ratio (OR) 3.6]; within the first month, use of split allografts (OR 2.9); and within the first year, use of a liver donated after cardiac death (OR 4.9). Each of the three high‐risk periods within the first year had distinct causes of graft failure, risk factors for retransplantation, and survival rates after retransplantation.